Crosslinked bipolar membrane as well as preparation method and application thereof

By adopting a crosslinked bipolar membrane and using the combination of crosslinked base membrane, cation exchange membrane and anion exchange membrane, the problems of low efficiency and poor stability of hydrochloric acid and sodium hydroxide formation in bipolar membrane electrodialysis are solved, efficient and stable hydrochloric acid and sodium hydroxide formation are achieved, and the service life of the bipolar membrane is extended.

CN119633619AActive Publication Date: 2025-03-18TONGZHOU ZONGHENG (XIAMEN) FLUID TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411827672.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing bipolar membrane electrodialysis method has low efficiency and poor stability when producing hydrochloric acid and sodium hydroxide, and the bipolar membrane life is short, and the generation efficiency is significantly reduced with the extension of use time.

Method used

Crosslinked bipolar membranes are used, including crosslinked base membranes, cation exchange membranes and anion exchange membranes, and the acid and alkali resistance and impact resistance of the bipolar membranes are improved through the use of specific polymer structures and MOF materials.

Benefits of technology

It realizes continuous and efficient production of hydrochloric acid and sodium hydroxide in production wastewater containing high concentrations of salt, extends the service life of the bipolar membrane and improves the stability and efficiency of the products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633619A_ABST
    Figure CN119633619A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of compound preparation, and relates to a cross-linked bipolar membrane as well as a preparation method and application thereof. The cross-linked bipolar membrane comprises a cross-linked base membrane as well as a cation exchange membrane and an anion exchange membrane which are respectively positioned on two side surfaces of the cross-linked base membrane; the cross-linked base membrane is prepared according to the following method: impregnating a high molecular weight polyethylene supporting layer in a polymeric monomer impregnation liquid containing low molecular weight polyethylene, styrene, divinyl benzene, an initiator and an MOF material, and performing polymerization reaction on the supporting layer in an inert atmosphere after the impregnation is completed, so as to obtain the cross-linked base membrane; the cation exchange membrane is formed by a polymer I; the anion exchange membrane is formed by a polymer II, and the polymer II is a copolymer obtained through a copolymerization reaction of diallyldimethylammonium chloride and allyltrimethyl ammonium chloride. When the cross-linked bipolar membrane provided by the invention is used for electrolyzing production wastewater containing high-concentration salt by a bipolar membrane electrodialysis method, hydrochloric acid and sodium hydroxide can be continuously and efficiently obtained, and the application prospect is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of compound preparation and relates to a cross-linked bipolar membrane and a preparation method and application thereof. Background Art

[0002] Hydrochloric acid is an aqueous solution of hydrogen chloride, which is a colorless liquid. Hydrochloric acid has a wide range of uses in biology, industry, and daily life. For example, in the biological field, hydrochloric acid is one of the main components of gastric acid, which can promote the conversion of pepsinogen into active pepsin and provide the necessary acidic environment, promote the decomposition of substances such as protein, fat, and starch, and play a role in promoting digestion; hydrochloric acid is an important component of the intestinal mucosal barrier, which can prevent the invasion or colonization of potential pathogens, maintain the function and structural integrity of the intestinal mucosal barrier, and kill bacteria that enter the stomach with food; hydrochloric acid can also enter the small intestine to cause the release of secretin and cholecystokinin, promote the secretion of pancreatic juice, bile, and small intestinal juice, thereby promoting the digestion process. In the industrial field, hydrochloric acid, as a strong acid, can be used to neutralize various alkali solutions and adjust the pH value of the solution; hydrochloric acid is often used for pickling steel, removing oxides and rust on the surface of steel, and improving the surface quality and subsequent processing performance of steel; hydrochloric acid is an important raw material for manufacturing a variety of chemical products, such as fertilizers (nitrogen fertilizers, phosphate fertilizers), plastics (polyvinyl chloride PVC), dyes, etc. In daily life, hydrochloric acid can not only be used to make cleaning agents such as toilet cleaners to effectively remove various stains and dirt, but can also be used to remove rust on metal surfaces to restore the gloss and performance of the metal surface.

[0003] Sodium hydroxide, also known as caustic soda, caustic soda or caustic soda, is a strong alkaline compound with a wide range of uses. Hydrochloric acid has a wide range of uses in industry, food, and daily life. In industry, sodium hydroxide can be used to treat natural fibers such as cotton and linen, remove non-fibrous substances such as cottonseed hulls and wax, and improve the quality of textiles; sodium hydroxide can be used as a sizing agent for fabrics to make the fabrics soft and breathable and prevent hair loss, and can also be used to bleach textiles such as silk; sodium hydroxide is the basic raw material for the production of a variety of chemical products, and can be used to produce chemicals such as borax, sodium cyanide, formic acid, oxalic acid, and phenol. In food, sodium hydroxide can be used as a food processing aid, used in container cleaning, starch processing, preparation of carboxymethyl cellulose, manufacturing of sodium glutamate, etc., used as a food acidity regulator, leavening agent, etc., as a peeling agent for citrus, peaches, etc. In daily life, sodium hydroxide is one of the raw materials for making soaps and detergents.

[0004] Using bipolar membrane electrodialysis to treat high-concentration production wastewater is one of the methods for co-producing hydrochloric acid and sodium hydroxide. Although bipolar membrane electrodialysis has the advantages of low energy consumption, simple operation and easy scale-up compared to chemical synthesis for preparing hydrochloric acid and sodium hydroxide, it cannot efficiently produce hydrochloric acid and sodium hydroxide, and the life of the bipolar membrane is short. As the bipolar membrane is used for a longer time, the production efficiency of hydrochloric acid and sodium hydroxide will drop significantly, and the stability is poor. Summary of the invention

[0005] The first object of the present invention is to provide a cross-linked bipolar membrane that can improve the production efficiency of hydrochloric acid and sodium hydroxide and has poor stability.

[0006] The second object of the present invention is to provide a method for preparing the above cross-linked bipolar membrane.

[0007] The third object of the present invention is to provide an application of the cross-linked bipolar membrane in resource recovery of production wastewater containing high-concentration salt.

[0008] Specifically, the cross-linked bipolar membrane provided by the present invention comprises a cross-linked base membrane and a cation exchange membrane and an anion exchange membrane respectively located on the two side surfaces of the cross-linked base membrane; the cross-linked base membrane is prepared according to the following method: a high molecular weight polyethylene support layer is immersed in a polymer monomer impregnation solution containing low molecular weight polyethylene, styrene, divinylbenzene, an initiator and MOF material, and after the impregnation is completed, the support layer is subjected to a polymerization reaction under an inert atmosphere to obtain a cross-linked base membrane; the cation exchange membrane is formed by a polymer I having a structure shown in formula (1); the anion exchange membrane is formed by a polymer II, and the polymer II is a copolymer obtained by copolymerizing diallyldimethylammonium chloride and allyltrimethylammonium chloride in a molar ratio of 1:(0.01-0.1);

[0009]

[0010] The method for preparing a cross-linked bipolar membrane provided by the present invention comprises the following steps:

[0011] S21. Immersing a high molecular weight polyethylene support layer in a polymerizing monomer impregnation solution containing low molecular weight polyethylene, styrene, divinylbenzene, an initiator and MOF materials, and after the impregnation is completed, subjecting the support layer to a polymerization reaction under an inert atmosphere to obtain a cross-linked base membrane; feeding butadiene into an organic solvent for a polymerization reaction, and then subjecting the obtained polybutadiene to a thiol-ene click reaction with sodium 3-(5-mercapto-1-tetrazolyl)benzenesulfonate to obtain a solution containing polymer I; spraying the solution containing polymer I on the surface of the substrate and drying it, and then peeling the membrane layer from the surface of the substrate to obtain a cation exchange membrane; feeding diallyldimethylammonium chloride, allyltrimethylammonium chloride and an inorganic peroxide initiator in a molar ratio of 1:(0.01-0.1):(0.001-0.01) into an organic solvent for a copolymerization reaction to obtain a solution containing a copolymer; spraying the solution containing the copolymer on the surface of the substrate and drying it, and then peeling the membrane layer from the surface of the substrate to obtain an anion exchange membrane;

[0012] S22. The cation exchange membrane and the anion exchange membrane are respectively bonded to the upper and lower surfaces of the cross-linked base membrane and then hot-pressed to obtain a cross-linked bipolar membrane.

[0013] The key to the present invention is to use a specific cross-linked base membrane as a substrate, to form a cation exchange membrane using a polymer having formula (1), and to form an anion exchange membrane using a copolymer of diallyldimethylammonium chloride and allyltrimethylammonium chloride. The cross-linked bipolar membrane thus obtained can continuously and efficiently obtain hydrochloric acid and sodium hydroxide when used for bipolar membrane electrodialysis of industrial wastewater containing high-concentration salt. The reason for this may be that: on the one hand, the MOF material can improve the efficiency of bipolar membrane water electrolysis, and can provide a buffer for the Cl in the acid chamber. - More H + , and is Na in the base chamber + Provide more OH - , which can promote the synthesis of hydrochloric acid and sodium hydroxide; on the other hand, the existing bipolar membranes are usually based on aromatic carbon skeletons, but the carbon-oxygen bonds in the aromatic carbon skeletons are easily affected by the H generated by the bipolar membrane. + and OH - However, high molecular weight polyethylene, polymers formed by polymerization of low molecular weight polyethylene and styrene and divinylbenzene, polymer I, copolymers of diallyldimethylammonium chloride and allyltrimethylammonium chloride all have carbon-carbon double bond main chains and are not easily attacked by H. + and OH - At the same time, the side chain of the polymer having the structure shown in formula (1) is evenly distributed with sodium benzenesulfonate groups and nitrogen heterocyclic functional groups. The presence of nitrogen heterocyclic functional groups can make the electron distribution of the polymer more uniform, thereby giving the polymer stronger acid and alkali resistance, making the bipolar membrane more stable in high concentration H + and OH- Furthermore, the polymer shown in formula (1) has a relatively flexible main chain provided by CC and a relatively rigid side chain provided by the sodium benzenesulfonate group / nitrogen heterocyclic functional group. The flexible main chain can improve the impact resistance of the bipolar membrane, making it have good tolerance to the flow of liquid during use, while the introduction of rigid side chains and cross-linked polystyrene / divinylbenzene in the cross-linked base membrane and cross-linked polydiallyldimethylammonium chloride / allyltrimethylammonium chloride in the anion exchange membrane can synergistically improve the support force of the cross-linked bipolar membrane, making the bipolar membrane less susceptible to the impact of liquid flow disturbance and affecting its service life.

[0014] In a preferred embodiment, the MOF material is a modified MOF material obtained by co-modification of Fe and Cu. In this case, the production efficiency of hydrochloric acid and sodium hydroxide can be further improved. It is speculated that the reason may be that iron ions and copper ions can synergistically increase the reaction activity of water, weaken molecular bonds, and accelerate the dissociation of water in the middle layer of the bipolar membrane into H + and OH - , thereby promoting the synthesis of hydrochloric acid and sodium hydroxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of the structure of the two-compartment bipolar membrane electrodialysis device used in the test example. DETAILED DESCRIPTION

[0016] The cross-linked bipolar membrane provided by the present invention comprises a cation exchange membrane, a cross-linked base membrane and an anion exchange membrane which are stacked in sequence; the cation exchange membrane is formed by polymer I, and the anion exchange membrane is formed by polymer II. In a preferred embodiment, the thickness of the cation exchange membrane is 5 to 20 microns, specifically 5 microns, 8 microns, 10 microns, 12 microns, 15 microns, 18 microns, 20 microns or any value therebetween; the thickness of the cross-linked base membrane is 10 to 30 microns, specifically 10 microns, 12 microns, 15 microns, 18 microns, 20 microns, 22 microns, 24 microns, 26 microns, 28 microns, 30 microns or any value therebetween; the thickness of the anion exchange membrane is 5 to 20 microns, specifically 5 microns, 8 microns, 10 microns, 12 microns, 15 microns, 18 microns, 20 microns or any value therebetween.

[0017] In the present invention, the cross-linked base film is prepared according to the following method: the high molecular weight polyethylene support layer is immersed in a polymer monomer impregnation solution containing low molecular weight polyethylene, styrene, divinylbenzene, initiator and MOF material, and after the impregnation is completed, the support layer is subjected to polymerization reaction under an inert atmosphere to obtain a cross-linked base film. In the formation process of the cross-linked base film, low molecular weight polyethylene, styrene and divinylbenzene can form cross-linked polymers on the surface and inside of the high molecular weight polyethylene support layer, thereby enhancing the mechanical strength of the high molecular weight polyethylene support layer. Among them, the number average molecular weight of the high molecular weight polyethylene in the high molecular weight polyethylene support layer is preferably 10000 to 50000, and can specifically be 10000, 15000, 20000, 25000, 30000, 35000, 40000, 45000, 50000 or any value therebetween. The mass ratio of low molecular weight polyethylene, styrene, divinylbenzene, initiator and MOF material in the polymer monomer impregnation solution is preferably 100: (50-80): (5-10): (1-5): (10-20). Taking the amount of low molecular weight polyethylene as 100 parts by weight, the amount of styrene is preferably 50-80 parts by weight, specifically 50, 55, 60, 65, 70, 75, 80 parts by weight or any value therebetween; the amount of divinylbenzene is preferably 5-10 parts by weight, such as 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 parts by weight or any value therebetween; the content of the initiator is preferably 1-5 parts by weight, such as 1, 2, 3, 4, 5 parts by weight or any value therebetween; the amount of the MOF material is preferably 10-20 parts by weight, such as 10, 12, 14, 16, 18, 20 parts by weight or any value therebetween. The number average molecular weight of the low molecular weight polyethylene is preferably 1000 to 5000, specifically 1000, 2000, 3000, 4000, 5000 or any value therebetween. The initiator is preferably an azo initiator, such as at least one of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), dimethyl azobisisobutyrate (AIBME) and azoisobutylcyanamide (V30).

[0018] In the present invention, the MOF material may be an unmodified MOF material or a modified MOF material. The modified MOF material may be a Fe-modified MOF material, and is particularly preferably a Fe and Cu co-modified MOF material.

[0019] In a preferred embodiment, the Fe and Cu co-modified MOF material is prepared according to the following method: S11. 3,5-pyrazole dicarboxylic acid is dispersed in an alkaline solution, aluminum chloride is added to the obtained dispersion and stirred until dissolved, and then the obtained solution is heated at 90-110°C for 10-48 hours and filtered, and the obtained precipitate is dried to obtain a MOF carrier; S12. The MOF carrier is activated at 140-160°C for 10-24 hours, and then the obtained activated MOF carrier is dispersed in an organic solvent with iron nitrate and copper nitrate, and then the temperature is raised to 60-80°C for reaction for 10-48 hours, and after the reaction is completed, it is cooled to room temperature to obtain a solution containing a modified MOF material. Among them, the mass ratio of the MOF carrier, iron nitrate and copper nitrate is preferably 1: (0.5-0.8): (0.1-0.3). Specifically, based on 1 part by weight of the MOF carrier, the amount of ferric nitrate is 0.5 to 0.8 parts by weight, such as 0.5, 0.6, 0.7, 0.8 parts by weight or any value therebetween; the amount of copper nitrate is 0.1 to 0.3 parts by weight, such as 0.1, 0.15, 0.2, 0.25, 0.3 parts by weight or any value therebetween.

[0020] In the present invention, the cation exchange membrane is formed by polymer I having a structure represented by formula (1).

[0021]

[0022] The present invention has no particular limitation on the source of polymer I, as long as it has the structure shown in formula (1). In a preferred embodiment, the polymer I is prepared by the following method: butadiene is added to an organic solvent for polymerization reaction, and the obtained polybutadiene is subjected to a thiol-ene click reaction with sodium 3-(5-mercapto-1-tetrazolyl)benzenesulfonate to obtain a solution containing polymer I. Wherein, the conditions of the polymerization reaction preferably include a polymerization temperature of 50 to 100°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or any value therebetween; a polymerization pressure of 0.1 to 0.5 MPa, such as 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa or any value therebetween; and a polymerization time of 0.5 to 10 h, such as 0.5 h, 1 h, 2 h, 4 h, 6 h, 8 h, 10 h or any value therebetween. The molar ratio of butadiene to sodium 3-(5-mercapto-1-tetrazolyl)benzenesulfonate is preferably (0.9-1.1):1, such as 0.9:1, 0.95:1, 1:1, 1.05:1, 1.1:1 or any value therebetween. The conditions for the mercapto-ene click reaction preferably include a temperature of 70-100°C, such as 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C or any value therebetween; a polymerization pressure of 0.1-0.5MPa, such as 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa or any value therebetween; and a polymerization time of 0.5-5h, such as 0.5h, 1h, 2h, 4h, 5h or any value therebetween.

[0023] In the present invention, the anion exchange membrane is formed by polymer II, which is a copolymer obtained by copolymerization of diallyldimethylammonium chloride (having a structure shown in formula (2)) and allyltrimethylammonium chloride (having a structure shown in formula (3)) in a molar ratio of 1:(0.01-0.1). The copolymer is a cross-linked polymer. Among them, the conditions of the copolymerization reaction preferably include a copolymerization temperature of 50-100°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, 100°C or any value therebetween; a copolymerization pressure of 0.1-0.5MPa, such as 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa or any value therebetween; and a copolymerization time of 0.5-10h, such as 0.5h, 1h, 2h, 4h, 6h, 8h, 10h or any value therebetween. The copolymerization reaction is generally carried out in the presence of an inorganic peroxide initiator. The inorganic peroxy initiator may include at least one of potassium persulfate, sodium persulfate, ammonium persulfate and the like.

[0024]

[0025] In the present invention, the terms "I" and "II" are only used to distinguish the same substance appearing at different times for the convenience of description and have no other special meanings. In addition, the pressures are all gauge pressures.

[0026] The method for preparing a cross-linked bipolar membrane provided by the present invention comprises the following steps:

[0027] S21. Immersing a high molecular weight polyethylene support layer in a polymerizing monomer impregnation solution containing low molecular weight polyethylene, styrene, divinylbenzene, an initiator and MOF materials, and after the impregnation is completed, subjecting the support layer to a polymerization reaction under an inert atmosphere to obtain a cross-linked base membrane; feeding butadiene into an organic solvent for a polymerization reaction, and then subjecting the obtained polybutadiene to a thiol-ene click reaction with sodium 3-(5-mercapto-1-tetrazolyl)benzenesulfonate to obtain a solution containing polymer I; spraying the solution containing polymer I on the surface of the substrate and drying it, and then peeling the membrane layer from the surface of the substrate to obtain a cation exchange membrane; feeding diallyldimethylammonium chloride, allyltrimethylammonium chloride and an inorganic peroxide initiator in a molar ratio of 1:(0.01-0.1):(0.001-0.01) into an organic solvent for a copolymerization reaction to obtain a solution containing a copolymer; spraying the solution containing the copolymer on the surface of the substrate and drying it, and then peeling the membrane layer from the surface of the substrate to obtain an anion exchange membrane;

[0028] S22. The cation exchange membrane and the anion exchange membrane are respectively bonded to the upper and lower surfaces of the cross-linked base membrane and then hot-pressed to obtain a cross-linked bipolar membrane.

[0029] In the above-mentioned preparation process of the cross-linked bipolar membrane, in step S11, the preparation materials and conditions of the cross-linked base membrane, polymer I and copolymer have been described above and will not be repeated here.

[0030] In the preparation process of the above-mentioned cross-linked bipolar membrane, in step S22, the hot pressing conditions preferably include a hot pressing temperature of 200-400°C, such as 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C or any value therebetween; a hot pressing pressure of 5-20MPa, such as 5MPa, 8MPa, 10MPa, 12MPa, 14MPa, 16MPa, 18MPa, 20MPa or any value therebetween; and a hot pressing time of 10-60min, such as 10min, 20min, 30min, 40min, 50min, 60min or any value therebetween.

[0031] The present invention also provides the use of the cross-linked bipolar membrane in resource recovery of production wastewater containing high-concentration salt, wherein the production wastewater containing high-concentration salt can be, for example, concentrated seawater.

[0032] The present invention will be described in detail below through examples.

[0033] Preparation Example 1-1

[0034] Butadiene was added to toluene and reacted at a temperature of 100°C and a pressure of 0.1 MPa for 0.5 h. Sodium 3-(5-mercapto-1-tetrazolyl)benzenesulfonate was added to the obtained polybutadiene solution, and then the mixture was reacted at a temperature of 70°C and a pressure of 0.5 MPa for 5 h. The molar ratio of sodium 3-(5-mercapto-1-tetrazolyl)benzenesulfonate to butadiene was 1:1, and a solution containing polymer I with a concentration of 5 wt% was obtained.

[0035] Preparation Example 1-2

[0036] Butadiene was added to toluene and reacted at a temperature of 50°C and a pressure of 0.5 MPa for 10 hours. Sodium 3-(5-mercapto-1-tetrazolyl)benzenesulfonate was added to the obtained polybutadiene solution, and then the mixture was reacted at a temperature of 70°C and a pressure of 0.5 MPa for 5 hours. The molar ratio of sodium 3-(5-mercapto-1-tetrazolyl)benzenesulfonate to butadiene was 0.9:1, and a solution containing polymer I with a concentration of 10 wt% was obtained.

[0037] Preparation Example 1-3

[0038] Butadiene was added to toluene and reacted at a temperature of 80°C and a pressure of 0.3 MPa for 5 hours. Sodium 3-(5-mercapto-1-tetrazolyl)benzenesulfonate was added to the obtained polybutadiene solution, and then the reaction was carried out at a temperature of 80°C and a pressure of 0.3 MPa for 2 hours. The molar ratio of sodium 3-(5-mercapto-1-tetrazolyl)benzenesulfonate to butadiene was 0.9:1, and a solution containing polymer I with a concentration of 3 wt% was obtained.

[0039] Comparative Preparation Example 1-1

[0040] Butadiene was added to trichloroethane and reacted at a temperature of 100° C. and a pressure of 0.1 MPa for 0.5 h to obtain a reference solution containing polymer I with a concentration of 5 wt%.

[0041] Preparation Example 2-1

[0042] S11. 5 g of 3,5-pyrazoledicarboxylic acid monohydrate was dispersed in 1 L of a 0.3 wt % sodium hydroxide aqueous solution, 10 g of aluminum chloride was added to the obtained dispersion and stirred until dissolved, and then the obtained solution was heated at 90° C. for 48 h and filtered, and the obtained precipitate was vacuum dried at 60° C. for 2 h to obtain a MOF carrier;

[0043] S12. Activate the MOF carrier at 140°C for 24 hours, then disperse the obtained activated MOF carrier, iron nitrate and copper nitrate in acetonitrile in a mass ratio of 1:0.5:0.1, and then heat to 70°C for reaction for 24 hours. After the reaction is completed, cool to room temperature to obtain a solution containing modified MOF material with a concentration of 5wt%.

[0044] Preparation Example 2-2

[0045] S11. 5 g of 3,5-pyrazoledicarboxylic acid monohydrate was dispersed in 1 L of a 0.3 wt % sodium hydroxide aqueous solution, 10 g of aluminum chloride was added to the obtained dispersion and stirred until dissolved, and then the obtained solution was heated at 110° C. for 10 h and filtered, and the obtained precipitate was vacuum dried at 60° C. for 2 h to obtain a MOF carrier;

[0046] S12. The MOF carrier is activated at 160°C for 10 hours, and then the activated MOF carrier is dispersed in acetonitrile with iron nitrate and copper nitrate in a mass ratio of 1:0.8:0.3, and then the temperature is raised to 60°C for reaction for 48 hours. After the reaction is completed, it is cooled to room temperature to obtain a solution containing modified MOF material with a concentration of 5 wt%.

[0047] Preparation Example 2-3

[0048] S11. 5 g of 3,5-pyrazoledicarboxylic acid monohydrate was dispersed in 1 L of a 0.3 wt % sodium hydroxide aqueous solution, 10 g of aluminum chloride was added to the obtained dispersion and stirred until dissolved, and then the obtained solution was heated at 100° C. for 24 h and filtered, and the obtained precipitate was vacuum dried at 60° C. for 2 h to obtain a MOF carrier;

[0049] S12. Activate the MOF carrier at 150°C for 15 hours, then disperse the obtained activated MOF carrier, iron nitrate and copper nitrate in acetonitrile in a mass ratio of 1:0.6:0.2, and then heat to 80°C for reaction for 10 hours. After the reaction is completed, cool to room temperature to obtain a solution containing modified MOF material with a concentration of 5wt%.

[0050] Preparation Example 2-4

[0051] A solution containing a modified MOF material was prepared according to the method of Preparation Example 2-1, except that copper nitrate was replaced by the same weight portion of ferric nitrate. The remaining conditions were the same as those of Preparation Example 2-1, to obtain a solution containing a modified MOF material.

[0052] Example 1

[0053] S21. The high molecular weight polyethylene support layer (the number average molecular weight of the high molecular weight polymer contained therein is 30000) is immersed in a polymerized monomer impregnation liquid containing low molecular weight polyethylene (number average molecular weight is 2000), styrene, divinylbenzene, azobisisobutyronitrile and MOF material (obtained from Preparation Example 2-1), the mass ratio of low molecular weight polyethylene, styrene, divinylbenzene, azobisisobutyronitrile and MOF material is 100:50:5:1:10, the total concentration of the polymerized monomer impregnation liquid is 35wt% and the solvent contained therein is toluene. After the impregnation is completed, the support layer is taken out from the impregnation liquid and reacted for 10 hours at a temperature of 50°C and a pressure of 0.5MPa under a nitrogen atmosphere to obtain a cross-linked base film with a thickness of 10±0.5 microns.

[0054] The solution containing polymer I obtained in Preparation Example 1-1 was sprayed on the substrate surface and vacuum dried at 60°C for 2 hours. The membrane layer was then peeled off from the substrate surface to obtain a cation exchange membrane with a thickness of 20±0.5 μm.

[0055] Diallyldimethylammonium chloride, allyltrimethylammonium chloride and potassium persulfate were added to toluene at a molar ratio of 1:0.01:0.001, and reacted at a temperature of 50°C and a pressure of 0.5MPa for 10 hours to obtain a solution containing a copolymer. The solution containing the copolymer was sprayed on the surface of the substrate, vacuum dried at 60°C for 2 hours, and then the membrane layer was peeled off from the surface of the substrate to obtain an anion exchange membrane with a thickness of 20±0.5 microns.

[0056] S22. The cation exchange membrane and the anion exchange membrane are respectively bonded to the upper and lower surfaces of the cross-linked base membrane, and then hot-pressed at a temperature of 200° C. and a pressure of 20 MPa for 60 min to obtain a cross-linked bipolar membrane, which is recorded as JLM-001.

[0057] Example 2

[0058] S21. The high molecular weight polyethylene support layer (the number average molecular weight of the high molecular weight polymer contained therein is 30000) is immersed in a polymerized monomer impregnation liquid containing low molecular weight polyethylene (the number average molecular weight is 5000), styrene, divinylbenzene, azobisisobutyronitrile and MOF material (obtained from Preparation Example 2-2), the mass ratio of low molecular weight polyethylene, styrene, divinylbenzene, azobisisobutyronitrile and MOF material is 100:80:10:5:15, the total concentration of the polymerized monomer impregnation liquid is 25wt% and the solvent contained therein is toluene. After the impregnation is completed, the support layer is taken out from the impregnation liquid and reacted for 10 hours at a temperature of 50°C and a pressure of 0.5MPa under a nitrogen atmosphere to obtain a cross-linked base film with a thickness of 30±0.5 microns.

[0059] The solution containing polymer I obtained in Preparation Example 1-1 was sprayed on the substrate surface and vacuum dried at 60°C for 2 hours. The membrane layer was then peeled off from the substrate surface to obtain a cation exchange membrane with a thickness of 5±0.5 μm.

[0060] Diallyldimethylammonium chloride, allyltrimethylammonium chloride and potassium persulfate were added to toluene at a molar ratio of 1:0.1:0.01, and reacted at a temperature of 50°C and a pressure of 0.5MPa for 10 hours to obtain a solution containing a copolymer. The solution containing the copolymer was sprayed on the surface of the substrate, vacuum dried at 60°C for 2 hours, and then the membrane layer was peeled off from the surface of the substrate to obtain an anion exchange membrane with a thickness of 5±0.5 microns.

[0061] S22. The cation exchange membrane and the anion exchange membrane are respectively bonded to the upper and lower surfaces of the cross-linked base membrane, and then hot-pressed at a temperature of 400° C. and a pressure of 5 MPa for 10 min to obtain a cross-linked bipolar membrane, which is recorded as JLM-002.

[0062] Example 3

[0063] S21. The high molecular weight polyethylene support layer (the number average molecular weight of the high molecular weight polymer contained therein is 20000) is immersed in a polymerized monomer impregnation solution containing low molecular weight polyethylene (number average molecular weight is 3000), styrene, divinylbenzene, azobisisobutyronitrile and MOF material (obtained from Preparation Example 2-3), the mass ratio of low molecular weight polyethylene, styrene, divinylbenzene, azobisisobutyronitrile and MOF material is 100:60:8:2:15, the total concentration of the polymerized monomer impregnation solution is 30wt% and the solvent contained therein is toluene. After the impregnation is completed, the support layer is taken out from the impregnation solution and reacted for 10 hours at a temperature of 50°C and a pressure of 0.5MPa under a nitrogen atmosphere to obtain a cross-linked base film with a thickness of 20±0.5 microns.

[0064] The solution containing polymer I obtained in Preparation Example 1-1 was sprayed on the substrate surface and vacuum dried at 60°C for 2 hours. The membrane layer was then peeled off from the substrate surface to obtain a cation exchange membrane with a thickness of 10±0.5 μm.

[0065] Diallyldimethylammonium chloride, allyltrimethylammonium chloride and potassium persulfate were added to toluene at a molar ratio of 1:0.05:0.005, and reacted at a temperature of 50°C and a pressure of 0.5MPa for 10 hours to obtain a solution containing a copolymer. The solution containing the copolymer was sprayed on the surface of the substrate, vacuum dried at 60°C for 2 hours, and then the membrane layer was peeled off from the surface of the substrate to obtain an anion exchange membrane with a thickness of 10±0.5 microns.

[0066] S22. The cation exchange membrane and the anion exchange membrane are respectively bonded to the upper and lower surfaces of the cross-linked base membrane, and then hot-pressed at a temperature of 300° C. and a pressure of 10 MPa for 30 min to obtain a cross-linked bipolar membrane, which is recorded as JLM-003.

[0067] Example 4

[0068] A cross-linked bipolar membrane was prepared according to the method of Example 1, except that the solution containing the modified MOF material obtained in Preparation Example 2-1 was replaced by the solution containing the modified MOF material obtained in Preparation Example 2-4 in the same weight portion, and the other conditions were the same as in Example 1 to obtain a cross-linked bipolar membrane, which was recorded as JLM-004. The thickness of the cation exchange membrane was 20±0.5 microns, the thickness of the cross-linked base membrane was 10±0.5 microns, and the thickness of the anion exchange membrane was 20±0.5 microns.

[0069] Comparative Example 1

[0070] A cross-linked bipolar membrane was prepared according to the method of Example 1, except that the solution containing polymer I obtained in Preparation Example 1-1 was replaced by the reference solution containing polymer I obtained in Comparative Preparation Example 1-1 in the same weight portion, and the other conditions were the same as in Example 1 to obtain a reference cross-linked bipolar membrane, which was recorded as DJLM-001. The thickness of the cation exchange membrane was 20±0.5 microns, the thickness of the cross-linked base membrane was 10±0.5 microns, and the thickness of the anion exchange membrane was 20±0.5 microns.

[0071] Comparative Example 2

[0072] A cross-linked bipolar membrane was prepared according to the method of Example 1, except that in the preparation process of the anion exchange membrane, diallyldimethylammonium chloride was replaced by allyltrimethylammonium chloride in the same molar amount, and the other conditions were the same as in Example 1 to obtain a reference cross-linked bipolar membrane, which was recorded as DJLM-002. The thickness of the cation exchange membrane was 20±0.5 μm, the thickness of the cross-linked base membrane was 10±0.5 μm, and the thickness of the anion exchange membrane was 20±0.5 μm.

[0073] Test Case

[0074] This test example uses a two-compartment bipolar membrane electrodialysis device, the anode plate material is a mesh metal DSA, the cathode plate material is a mesh titanium electrode plate, the bipolar membrane and cation exchange membrane are BP-1 bipolar membrane and CMX cation exchange membrane ( CMX, ASTOM, Japan), membrane area 200cm 2 The membrane stack is composed of 10 groups of repeating units of B1C2 configuration.

[0075] like Figure 1As shown, a concentrated seawater solution with a NaCl concentration of 0.58 mol / L was introduced into the acid chamber inlet of the two-compartment bipolar membrane electrodialysis device, deionized water was introduced into the alkali chamber, and a 0.5 mol / L Na2SO4 solution was introduced into the polar liquid chamber. A DC power supply was turned on to perform constant voltage 12 V electrodialysis. After 30 minutes, the concentration of hydrochloric acid at the acid chamber outlet and the concentration of sodium hydroxide at the alkali chamber outlet were measured. The results are shown in Table 1.

[0076] After the bipolar membrane was used to electrodialyze seawater continuously for half a year, the concentration of hydrochloric acid at the outlet of the acid chamber and the concentration of sodium hydroxide at the outlet of the alkali chamber after the electrodialysis were determined according to the above method. The results are shown in Table 1.

[0077] Table 1

[0078]

[0079] From the results of Examples 1 to 4 and Comparative Examples 1 to 2, it can be seen that the use of the cross-linked bipolar membrane provided by the present invention for electrolyzing seawater by bipolar membrane electrodialysis can continuously and efficiently obtain hydrochloric acid and sodium hydroxide. From the comparison between Example 1 and Example 4, it can be seen that when the MOF material is co-modified with Fe and Cu, it is more conducive to promoting the synthesis of hydrochloric acid and sodium hydroxide.

[0080] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A cross-linked bipolar membrane, characterized in that: The cross-linked bipolar membrane comprises a cross-linked base membrane and a cation exchange membrane and an anion exchange membrane respectively located on both sides of the cross-linked base membrane; The cross-linked base membrane is prepared according to the following method: a high molecular weight polyethylene support layer is immersed in a polymerizing monomer impregnation solution containing low molecular weight polyethylene, styrene, divinylbenzene, an initiator and MOF materials, and after the impregnation is completed, the support layer is subjected to a polymerization reaction under an inert atmosphere to obtain a cross-linked base membrane; The cation exchange membrane is formed by a polymer I having a structure shown in formula (1); The anion exchange membrane is formed by polymer II, which is a copolymer obtained by copolymerization of diallyldimethylammonium chloride and allyltrimethylammonium chloride in a molar ratio of 1:(0.01-0.1); 2. The cross-linked bipolar membrane according to claim 1, characterized in that The thickness of the cation exchange membrane is 5 to 20 microns, the thickness of the cross-linked base membrane is 10 to 30 microns, and the thickness of the anion exchange membrane is 5 to 20 microns.

3. The cross-linked bipolar membrane according to claim 1, characterized in that The number average molecular weight of the high molecular weight polyethylene in the high molecular weight polyethylene support layer is 10000 to 50000; Preferably, the mass ratio of low molecular weight polyethylene, styrene, divinylbenzene, initiator and MOF material in the polymerized monomer impregnation solution is 100:(50-80):(5-10):(1-5):(10-20); Preferably, the number average molecular weight of the low molecular weight polyethylene is 1000 to 5000; Preferably, the initiator is an azo initiator; Preferably, the polymerization reaction conditions include a polymerization temperature of 50 to 100° C., a polymerization pressure of 0.1 to 0.5 MPa, and a polymerization time of 0.5 to 10 h.

4. The cross-linked bipolar membrane according to any one of claims 1 to 3, characterized in that: The MOF material is a modified MOF material obtained by co-modification with Fe and Cu.

5. The cross-linked bipolar membrane according to claim 4, characterized in that The modified MOF material is prepared according to the following method: S11. 3,5-pyrazoledicarboxylic acid is dispersed in an alkaline solution, aluminum chloride is added to the obtained dispersion and stirred until dissolved, and then the obtained solution is heated at 90 to 110° C. for 10 to 48 hours and filtered, and the obtained precipitate is dried to obtain a MOF carrier; S12. Activate the MOF carrier at 140-160° C. for 10-24 h, disperse the activated MOF carrier with ferric nitrate and copper nitrate in an organic solvent, heat to 60-80° C. for reaction for 10-48 h, and cool to room temperature after the reaction to obtain a solution containing a modified MOF material; Preferably, the mass ratio of the MOF carrier, ferric nitrate and copper nitrate is 1:(0.5-0.8):(0.1-0.3).

6. The cross-linked bipolar membrane according to any one of claims 1 to 3, characterized in that: The polymer I is prepared by the following method: adding butadiene into an organic solvent for polymerization reaction, and then subjecting the obtained polybutadiene to a thiol-ene click reaction with sodium 3-(5-mercapto-1-tetrazolyl)benzenesulfonate to obtain a solution containing the polymer I; Preferably, the polymerization reaction conditions include a polymerization temperature of 50 to 100° C., a polymerization pressure of 0.1 to 0.5 MPa, and a polymerization time of 0.5 to 10 h; Preferably, the molar ratio of butadiene to sodium 3-(5-mercapto-1-tetrazolyl)benzenesulfonate is (0.9-1.1):1; Preferably, the conditions of the thiol-ene click reaction include a temperature of 70 to 100° C., a pressure of 0.1 to 0.5 MPa, and a time of 0.5 to 5 h.

7. The cross-linked bipolar membrane according to any one of claims 1 to 3, characterized in that: The copolymerization reaction conditions include a copolymerization temperature of 50 to 100° C., a copolymerization pressure of 0.1 to 0.5 MPa, and a copolymerization time of 0.5 to 10 h; Preferably, the copolymerization reaction is carried out in the presence of an inorganic peroxide initiator.

8. The method for preparing a cross-linked bipolar membrane according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: S21. The high molecular weight polyethylene support layer is immersed in a polymerizing monomer impregnation solution containing low molecular weight polyethylene, styrene, divinylbenzene, an initiator and MOF materials. After the impregnation is completed, the support layer is polymerized under an inert atmosphere to obtain a cross-linked base film; The butadiene is added into an organic solvent for polymerization reaction, and then the obtained polybutadiene is subjected to a thiol-ene click reaction with sodium 3-(5-mercapto-1-tetrazolyl)benzenesulfonate to obtain a solution containing polymer I; the solution containing polymer I is sprayed on the surface of a substrate and dried, and then the membrane layer is peeled off from the surface of the substrate to obtain a cation exchange membrane; Diallyldimethylammonium chloride, allyltrimethylammonium chloride and an inorganic peroxide initiator are added into an organic solvent in a molar ratio of 1:(0.01-0.1):(0.001-0.01) for copolymerization to obtain a solution containing a copolymer; the solution containing the copolymer is sprayed on a substrate surface and dried, and then the membrane layer is peeled off from the substrate surface to obtain an anion exchange membrane; S22. The cation exchange membrane and the anion exchange membrane are respectively bonded to the upper and lower surfaces of the cross-linked base membrane and then hot-pressed to obtain a cross-linked bipolar membrane.

9. The method for preparing a cross-linked bipolar membrane according to claim 8, characterized in that: The hot pressing conditions include a hot pressing temperature of 200 to 400° C., a hot pressing pressure of 5 to 20 MPa, and a hot pressing time of 10 to 60 minutes.

10. Use of the cross-linked bipolar membrane according to any one of claims 1 to 7 in resource recovery of production wastewater containing high-concentration salt.

Citation Information

Patent Citations

  • Single slice type ambipolar ion-exchange membrane and preparation method thereof

    CN101497001A

  • Method for preparing anion exchange membrane based on allyl monomer

    CN103755988A

  • Preparation method of bipolar membrane with same main chains of anion / cation exchange layers

    CN117181021A

  • Modified anion exchange membrane and preparation method thereof, bipolar membrane electrodialysis system and application of bipolar membrane electrodialysis system in preparation of lithium hydroxide

    CN118268051A

  • Bipolar membrane containing MOF (Metal Organic Framework) catalyst middle layer as well as preparation method and application of bipolar membrane

    CN118286869A